Management of meningococcal disease. Issue 5 (May 2019) - Sarfatti, Avishay; Nadel, Simon
Abstract: In recent years remarkable progress has been made in the development of vaccines against the different disease-causing serotypes of Neisseria meningitidis . Despite this, invasive meningococcal disease (IMD) remains a life-threatening illness with significant mortality, morbidity and long term sequelae. Prompt recognition and early treatment with antibiotics are the first steps in its management. Professionals looking after children with suspected IMD should be familiar with its clinical course, so that progression of the disease can be identified early, and its complications including septic shock, coagulopathy and raised intracranial pressure managed aggressively. This article summarizes the clinical features, presentation, pathophysiology and management of IMD focusing on its two common clinical presentations: septicaemia with associated shock and meningitis.